2021
DOI: 10.1186/s12889-021-10939-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk perceptions and attitudinal responses to COVID-19 pandemic: an online survey in Ethiopia

Abstract: Background Effective risk communication is one of the critical strategies in the response to COVID-19. This study examined risk perceptions and attitudinal responses to COVID-19 among the educated section of the society in Ethiopia. Methods An internet-based survey was conducted from April 22 to May 04, 2020, in Ethiopia. A questionnaire addressing the perception of health threat-combination of perceived vulnerability (PV) and perceived seriousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 40 publications
8
54
2
Order By: Relevance
“…Others also believe that COVID-19 is just a myth that does not exist in reality or is rhetorically fabricated by politicians to make money [43,44]. This chunk of misconception could be attributed to a lack of effective risk the rapid propagation of misinformation and misconception on the social media space and among the general population regarding COVID-19 [45]. As a result, they tend to discriminate or stigmatise people affected by the COVID-19 or survivors of the disease [32,46].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Others also believe that COVID-19 is just a myth that does not exist in reality or is rhetorically fabricated by politicians to make money [43,44]. This chunk of misconception could be attributed to a lack of effective risk the rapid propagation of misinformation and misconception on the social media space and among the general population regarding COVID-19 [45]. As a result, they tend to discriminate or stigmatise people affected by the COVID-19 or survivors of the disease [32,46].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…In terms of individual characteristics, it is found that demographic factors including gender, age, work, and residence during the pandemic have a significant effect on risk perception. The risk perception scores of people aged 18–28 are lower than those of older respondents who have a job and have a higher level of education have significantly higher risk perception scores than other respondents [ [17] , [18] , [19] ]. Demographic factors are the main determinants of COVID-19 risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence is scarce as to which of these factors contribute more to a practical adoption and adherence to such precautions. The few studies conducted previously were limited to subsets of the population, particularly health care workers [ 10 12 ]. This study aimed to investigate the level and factors associated with COVID-19 prevention practices among clients visiting a tertiary hospital in Addis Ababa.…”
Section: Introductionmentioning
confidence: 99%